Giant Renal Angiomyolipoma by the Example of Clinical Cases - S. V. Yadrentseva; N. V. Nudnov; Emil’ G. Gasymov (Вестник рентгенологии и радиологии)
The paper presents two clinical cases of patients with giant renal angiomyolipomas (AML), in one of whom its course was complicated by intratumoral hemorrhage. It describes key diagnostic criteria for computed tomography (CT), as well as the distinctive features of other neoplasms that should undergo a differential diagnosis. The similar clinical presentations and morphological characteristics of different renal neoplasms can cause certain diagnostic difficulties; however, the carefully collected historical data and distinctive criteria allow AML to be identified. Due to its high sensitivity and specificity, abdominal contrast-enhanced CT is an effective imaging technique in the detection and differential diagnosis of giant renal AML.